Comparison of Time Management Perception of Students Studying at Department of Physical Education and Sports Teaching and Program in Primary School Education - GUMUSGUL, Osman (Asian Journal of Education and Training, 2018)
The aim of this study was to compare time management perception of students studying at Department of Physical Education and Sports Teaching and program in Primary School Education. Totally, 170 students took part in this research. Data was gathered through Time Management Scale that had been developed by Britton and Tesser (1991) and was translated to Turkish Language by Alay and Koçak (2002). In evaluation part, frequency analysis and parametric tests were used. It was statistically determined that there were significant differences between students studying at department of physical education and sports teaching with program in primary school education. It is considered that the students of Physical Education and Sports Teaching Department have high perception in all three sub-dimensions because of their habit of using the time well in the competition or the habits of time planning such as nutrition and sleeping out of sporting time.